La importancia del pensamiento sistémico para el diseño de estrategias exitosas - Soto Quispe, Natalia (2021)
The word strategy, for many centuries, made reference only and exclusively to a military context. As the decades passed, people began to broaden the spectrum of strategy and transfer it to other areas. Since the technological development of the 20th century, drastic and constant changes have occurred as at no other time in history, forcing organizations to adapt: changes that, at the time of writing (2021), are still in the making. Therefore, the key question is how to achieve change without losing direction and meaning. To achieve this, constant change must be part of the very concept of strategy. The need arises to manage strategies in order to make them adaptable; and, to this end, it is essential to understand the systemic dynamics of the organizational structure. The latter, at the same time, needs an organizational purpose and a shared vision. Therefore, the central argument is that when the structure of the system is understood, a strategy can be designed according to the needs of the organization; in other words, strategy management can be developed in the right way.